Subjects of responsibility : framing personhood in modern bureaucracies - Parker, Andrew, 1953-; Sarat, Austin; Umphrey, Martha Merrill (Fordham University Press, 2011)
How and why has the concept of responsibility come to pervade the fabric of American public and private life? How are ideas of responsibility instantiated in, and constituted by, the workings of social and political institutions? What place do liberal discourses of responsibility, based on the individual, have in today's biopolitical world, where responsibility is so often a matter of risk assessment, founded in statistical probabilities?